RANCANG BANGUN LASER UNTUK PEMBELAJARAN OPTIKA DALAM MENENTUKAN INDEKS BIAS DAN DIFRAKSI KISI - Puji Hariati Winingsih (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2015)
This research is executed as a mean to make laser with energy  from ex- materials ( DVD) to be used to determine refractive index and  difraction. For that, have been made laser diode appliance network used to determine  \Kprism refractive index and laser wavelength [pass/through] difraction. This research is used by analysis with refractive index characteristic and difraction. Obtained result of that level of prism refractive index at variation of  i1  (30o, 45o dan 60o) equal to (1.53 ± 0.07), (1.45 ± 0.08) and ( 1.53 ± 0.08). Green Laser wavelength at variation of N (100, 300 and 600 line / mm)successively equal to (500 ± 0.03),   (525 ± 0.02) and (541 ± 0.07). Pursuant to prism refractive index theory of[is level of 1.5 and green colour laser wavelength range from (500 – 570) nm. So that can be concluded that result of research have as according to this appliance and theory have  earned to be told good to used in study of optics